2011
DOI: 10.2139/ssrn.1944825
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nash Equilibrium Under Adverse Selection

Abstract: This paper revisits the problem of adverse selection in the insurance market of Rothschild and Stiglitz [24]. We propose a simple extension of the game-theoretic structure in Hellwig [13] under which Nash-type strategic interaction between the informed customers and the uninformed firms results always in a particular separating equilibrium. The equilibrium allocation is unique and Pareto-efficient in the interim sense subject to incentive-compatibility and individual rationality. In fact, it is the unique ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Pursuing this line of research, Mimra and Wambach () have found that results similar to ours can be obtained in such a setting. Relatedly, Diasakos and Koufopoulos () have demonstrated that distinguishing between pre‐approved and standard applications for insurance and allowing firms to commit to not reject the applications for some contracts can yield similar results in a modified three stage game.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Pursuing this line of research, Mimra and Wambach () have found that results similar to ours can be obtained in such a setting. Relatedly, Diasakos and Koufopoulos () have demonstrated that distinguishing between pre‐approved and standard applications for insurance and allowing firms to commit to not reject the applications for some contracts can yield similar results in a modified three stage game.…”
Section: Resultsmentioning
confidence: 97%
“…We rule out the withdrawal of individual contracts mainly because, otherwise, firms would withdraw any loss‐making contract in stage 2, as pointed out by Grossman (), precluding any cross‐subsidization in equilibrium. Other ways around this problem have been suggested in recent complementary studies, for instance, by allowing for multiple withdrawal rounds with endogenous termination in Mimra and Wambach () or endogenous commitment not to withdraw individual contracts from a menu in Diasakos and Koufopoulos () . We abstract from this issue by ruling out partial withdrawal, but these papers show that analogous results can be obtained when this restriction is relaxed.…”
Section: A Game Theoretic Foundationmentioning
confidence: 99%
See 3 more Smart Citations